Game-based learning using visual spatial approach for children with autism to improve social development: a pilot study / Ilinadia Jamil...[et.al] - Jamil, Ilinadia; Mohamed Yussof, Fatrisha; Hassan, Nor Yus Shahirah; Azizuddin, Azzureen Nor Ain; Kadir, Zainal (2016)
Autism is a disorder in the growth and development of a brain or central nervous system that covers a large spectrum of impairment, symptoms and skills. The children who are suffering from autism face difficulties in communicating and adapting well in the community as they have trouble in understanding what others think and feel. However, children with learning disabilities appeared to have significant strengths in visual-spatial intelligence as they do the best when they deal with inductive learning and problem solving. This paper proposed a game-based learning application for autism children using visual spatial approach. Furthermore, this research aim is to provide a fun, interactive and engaging digital platform for learning basic knowledge such as alphabets, shapes and colors by using puzzle technique in manner it could cultivate interest in autism children as well as improvise social development. Several methods such as observation and references were used in the study. On the other hand, pilot test was conducted on 5 selected students from National Autism Society of Malaysia (NASOM) Melaka to identify the most suitable content in design and gameplay which can be developed to be compatible with autistic characters as well as to enhance their social skill and cognitive progress in future. Observation was conducted to understand their behavior in game engagement and obtain feedback of their needs and learning goals. Furthermore, the findings attached to the understanding that most of the respondents are impacted to the game play and fascinated with each element used in game design. Thus, the game prototype developed using visual spatial approach can slightly stimulate their social abilities and encourage children with autistic disorder to kindle a wide spectrum of skills. Moreover, future research is required to determine other factors contribute to the development of social and cognitive abilities for individuals with ASD.